2019
DOI: 10.1371/journal.pone.0226292
|View full text |Cite
|
Sign up to set email alerts
|

Omentin-1 in diabetes mellitus: A systematic review and meta-analysis

Abstract: ObjectivePrevious studies found inconsistent results on the relationship between diabetes mellitus and concentrations of omentin-1. This study performed a systematic review and meta-analysis to summarize previous findings on this relationship.MethodsStudies related to this outcome were obtained using a systematic search in the electronic databases of Cochrane Library, PubMed, Embase, SCOPUS, Google Scholar, gray literature and Web of Science in September 2019. The random effects model was used to measure the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 39 publications
1
32
0
Order By: Relevance
“…Significantly lower omentin-1 concentrations were observed in people with GDM or T2DM than in the controls by Pan et al, whereas no difference was found between the T1DM and controls [ 166 ]. Decreased omentin-1 concentrations may be an important indicator of gestational diabetes mellitus and type 2 diabetes mellitus.…”
Section: Clinical Applications Of Adipokines Measurements In Variomentioning
confidence: 99%
“…Significantly lower omentin-1 concentrations were observed in people with GDM or T2DM than in the controls by Pan et al, whereas no difference was found between the T1DM and controls [ 166 ]. Decreased omentin-1 concentrations may be an important indicator of gestational diabetes mellitus and type 2 diabetes mellitus.…”
Section: Clinical Applications Of Adipokines Measurements In Variomentioning
confidence: 99%
“…Simultaneously, the levels of anti-inflammatory adipokines, e.g., adiponectin, omentin decrease. The above biological events trigger a redox imbalance between ROS production and their scavenging, leading to induction of low grade chronic inflammation and intensification of OxS-paving the way for MetS [72,76,79,80]. These phenomena vastly affect WAT, which becomes insulin-resistant, and initiates hyperinsulinemia, enhances lipolysis, increases levels of circulating FFA and their deposition in muscles, liver and pancreas, followed by lipotoxicity, elevated production of glucose due to increased gluconeogenesis and glycogenolysis, and finally, systemic IR and HG [72,81].…”
Section: Hypertrophic Hypoxic and Inflamed White Adipose Tissue-thementioning
confidence: 99%
“…There are convincing data from experimental and clinical studies on the effects of omentin-1 on vascular reactivity and atherogenesis. Experimental studies have shown that omentin-1 causes vasodilation of isolated blood vessels of rats by increasing the activity of endothelial nitric oxide synthase and stimulates ischemia-induced revascularization in mice [4]. Omentin-1 modulates endothelial cell function and revascularization processes.…”
Section: Resultsmentioning
confidence: 99%